Latin American consensus on the treatment of melasma - Ocampo-Candiani, Jorge; Alas-Carbajal, Roberto; Bonifaz-Araujo, Jorge F.; Marín-Castro, Hernando; Valenzuela-Ahumada, Fernando; Véliz-Barandiarán, José Luis; Vila Echague, Agustina; Zepeda-Reyes, David E.; Miot, Helio A. [UNESP] (Wiley, 2025)
Melasma is a chronic, relapsing hyperpigmentation disorder that primarily affects photoexposed areas, occurring most frequently in adult women with darker skin phototypes. The primary factors contributing to its development include sun exposure, sex hormones (e.g., pregnancy), and genetic predisposition. Melasma is highly prevalent in Latin America, where many countries lie in intertropical zones and exhibit significant ethnic diversity because of centuries of intermixing among Native Americans, Europeans, and Sub-Saharan Africans. Nine Latin American experts formulated a DELPHI-based consensus to develop a valuable approach for treating melasma in this diverse population. After establishing an accurate diagnosis, assessing the impact on quality of life, and determining disease severity, the consensus recommends mitigating known triggers and promoting rigorous photoprotection. Active therapy should be tailored based on individual characteristics (e.g., pregnancy status, previous treatments, skin sensitivity). Treatment options include topical depigmenting agents, systemic therapies, and procedural interventions such as laser therapy, microneedling, and chemical peels. Periodic reassessment of the treatment is essential, with strategies adjusted if targeted outcomes are not achieved. Once clinical remission is attained, patients should continue using topical depigmenting agents and maintain strict photoprotection measures to prevent recurrence.
Keywords: consensus; Latin America; melanosis; melasma; therapy; topical drugs